Найти производную у'

0 голосов
10 просмотров

Найти производную у'


image
image
image

Математика (58 баллов) | 10 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
y = \frac{x^6+x^3-2}{ \sqrt{1-x^3} } = \frac{(x^3-1)(x^3+2)}{ \sqrt{1-x^3} } =\sqrt{1-x^3} (x^3+2)\\
y'= \frac{-3x^2(x^3+2)}{2 \sqrt{1-x^3} } +3x^2 \sqrt{1-x^3} = \frac{-6x^5-6x^2+6x^2-6x^5}{2 \sqrt{1-x^3} } =- \frac{6x^5}{ \sqrt{1-x^3} }

2) y' = 1 - \frac{6e^{2x}}{1+e^{2x}} - \frac{2e^x}{1+e^{2x}} = \frac{1+e^{2x}-6e^{2x}-2e^x}{1+e^{2x}} = \frac{1-5e^{2x}-2e^x}{1+e^{2x}}

3) прологарифмируем обе части:
lny = (lnx*sinx)ln(x*sinx)\\
 \frac{y'}{y} = ( \frac{sinx}{x}+lnx*cosx )ln(x*sinx)+(lnx*sinx) \frac{sinx+xcosx}{x*sinx} \\
y' = (x*sinx)^{lnx*sinx}*\\
*( \frac{sinx}{x}+lnx*cosx )ln(x*sinx)+(lnx*sinx) \frac{sinx+xcosx}{x*sinx})
(271k баллов)